Methodological issues in representing children's perspectives in transition research. Issue 5 (3rd September 2018) - Jadue Roa, Daniela Sofía; Whitebread, David; Gareca Guzmán, Benjamín
ABSTRACT: This article evidences the existing inter-relations between the rights perspective, the listening approach and participatory research with children, emphasising its contributions to the ECEC research field. Specifically, the contributions of visual participatory research in the field of early years transitions are discussed to illustrate the possibilities of research procedures aiming to introduce children's perspectives to the discussion. Principles established by the listening approach to research with children are reviewed and analysed from the rights' perspective established by the UNCRC and adopted in participatory research with children. We present a critical reflection about the methodological outcomes of two visual participatory transition studies carried out in Chile that aimed to gain a better understanding of children's perspectives about their transition experiences from Kindergarten to First Grade. Methodological contributions from both studies show that combining visual and narrative tools in research with children can help to further develop analysis strategies that are trustworthy and grounded in children's meanings.